1994
DOI: 10.1007/bf02090192
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of hepatic volumetry in fulminant hepatic failure

Abstract: Serial hepatic volumetry calculated from the liver area on abdominal computed tomography was performed in 19 patients with fulminant hepatic failure to determine a relationship between liver volume and prognosis. All patients received intensified artificial liver support comprised of plasma exchange and hemodiafiltration using high-performance membranes, and 10 patients survived. Liver volume was significantly larger in survivors than in nonsurvivors, both in an initial volumetry performed at the onset of coma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 16 publications
1
27
0
1
Order By: Relevance
“…Sekiyama et al [19] demonstrated that the computed tomography (CT)-derived liver volume (CTLV) of survivors of ALF was significantly greater than that of non-survivors. CTLV alone cannot reflect individual physical differences such as body weight and height, and it was therefore necessary to standardize individual liver volume in the healthy state.…”
Section: Introductionmentioning
confidence: 99%
“…Sekiyama et al [19] demonstrated that the computed tomography (CT)-derived liver volume (CTLV) of survivors of ALF was significantly greater than that of non-survivors. CTLV alone cannot reflect individual physical differences such as body weight and height, and it was therefore necessary to standardize individual liver volume in the healthy state.…”
Section: Introductionmentioning
confidence: 99%
“…The development of computer-based image processing techniques now allows for rapid and accurate assessment of spleen volumes on radiologic data [36] and their inclusion in the radiologist’s interpretation and report. While several papers have investigated spleen size nomograms using the volume [27,28,29,30,43,44,50], our study proposes and evaluates the systematic definition of a volumetric threshold to detect and grade splenomegaly.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] In addition to diagnosis, organ volume/height measurements have also been found to be important in making surgical decisions involving organ transplantation. [8][9][10] In traditional clinical practice, 3D organ analysis is performed via time-consuming manual measurements; alternatively, the evaluation is based on 2D projection images, which introduces bias.…”
Section: Introductionmentioning
confidence: 99%